2001
DOI: 10.1002/jsfa.1000
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sensory properties of popcorn from various types and sizes of kernel

Abstract: Three rice-type popcorns (red, white and yellow) and one pearl-type popcorn (yellow) were used in this study. All types were sized into three fractions (5 < D < 6 mm, 6 < D < 7 mm and D > 7 mm) by screening with round-hole sieves. Samples were tested for popping quality and suitability for popping, and the sensory properties of the popcorns were evaluated. A popcorn popper with a maximum operating temperature of 226°C was used for popping the samples (25 g). Both kernel type and size affected the expansion vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
38
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 9 publications
6
38
1
Order By: Relevance
“…In contrary, Tian et al (2001) found that kernel size had no effect. Ceylan and Karababa (2002) also concluded the smallest sized (5 < D < 6 mm) fraction gave the highest expansion volume and lowest number of unpopped kernels. Haugh et al (1976) and Pordesimo et al (1990) reported that kernel sphericity was related to expansion volume.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In contrary, Tian et al (2001) found that kernel size had no effect. Ceylan and Karababa (2002) also concluded the smallest sized (5 < D < 6 mm) fraction gave the highest expansion volume and lowest number of unpopped kernels. Haugh et al (1976) and Pordesimo et al (1990) reported that kernel sphericity was related to expansion volume.…”
Section: Introductionmentioning
confidence: 89%
“…Many studies have indicated that popping properties were mostly affected by physical properties of the popcorn kernels. These physical properties include kernel size (Allred-Coyle, Toma, Reiboldt, & Thakur, 2000;Ceylan & Karababa, 2002;Eldredge & Lyerly, 1943;Haugh, Lien, Hanes, & Ashman, 1976;Lin & Anantheswaran, 1988;Lyerly, 1942;Pordesimo, Anantheswaran, Fleischmann, Lin, & Hanna, 1990;Song et al, 1991;Tian, Buriak, & Eckhoff, 2001;Willier & Brunson, 1927), kernel sphericity (Eldredge & Lyerly, 1943;Haugh et al, 1976;Hoseney, Zeleznak, & Abdelrahman, 1983;Lyerly, 1942;Pordesimo et al, 1990;Tian et al, 2001;Willier & Brunson, 1927) kernel density (Chang, 1988;Haugh et al, 1976;Lyerly, 1942;Tian et al, 2001) and test weight (Eldredge & Thomas, 1959;Eldredge & Lyerly, 1943;Haugh et al, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Unpopped kernels were counted and recorded. The expansion volume, percentage of unpopped kernels (PUK), and flake size were determined by using methods described by Dofing et al (1990), Mohamed et al (1993) and Ceylan and Karababa (2002). …”
Section: Sample Preparation and Popping Methodsmentioning
confidence: 99%
“…Popcorn quality is measured primarily by the expansion volume and the number of unpopped kernels (Song, Eckhoff, Paulsen, & Litchfield, 1991). The expansion volume is a very important quality criterion commercially, because commercial popcorn buyers buy by weight and sell the popped corn by volume (Ceylan & Karababa, 2002). Like other corn types, yield is very important, but popping expansion has to good.…”
Section: Introductionmentioning
confidence: 99%
“…Although the increase of productivity is always desired, it is the expansion capacity that plays a decisive role in commercial value of popcorn (Ceylan and Karababa, 2002); there is no information in the literature regarding the effects of N and its application forms on the expansion capacity index of popcorn. Among the producers of popcorn, it is observed that it is common to use technical recommendations of fertilizer for common corn and popcorn.…”
Section: Introductionmentioning
confidence: 99%